Does current demographic policy in Russia impact on fertility of different educational groups? - Irina E. Kalabichina; Alla Tyndik (Russian Presidential Academy of National Economy and Public Administration (RANEPA), 2014)
This article is devoted to investigation current demographic policy in Russia impact on fertility of different educational groups. Authors use qualitative and quantitative data. Quantitative data for this analysis come from the Gender and Generation Survey in Russia (2004, 2007, 2011 waves). Semi-structured interview method (Moscow, 2010) was used to assess the cognitive and emotional aspects of fertility behaviour (to give birth the next child). One of the important results of this study that Russian population could not be satisfated with current demographic policy. Moreover, higher educated people have stronger demand for family-work measures to reach desired family size. People with higher education estimate influence of existing measures lower as a whole, but influence of potential measures (directed on combination of career and parenthood) the estimated higher.
Keywords: J13; J16; J18; 330; demographic policy; fertility; Russia